Implementasi Jelajah Alam Sekitar Untuk Siswa Kelas X Di Sekolah Menengah Atas Terhadap Hasil Belajar Biologi - Suci Mauliana; Devie Novallyan; Shalahuddin (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, 2023)
The problem in this study is that the learning carried out is still using a conventional approach so that communication only occurs in one direction which results in less active students in teaching and learning activities.Therefore, this research was carried out with the aim of knowing the effect of the application of Natural Surroundings (JAS) on the learning outcomes of class X students at State Senior High School 9 Tanjung Jabung Timur in Biology Subjects. The type of research used is quantitative research with interview instruments, tests, and documentation. The data analysis technique used is the normality test, homogeneity test and hypothesis testing. Researchers took the entire population as a sample. The total sampling is 68 students. 34 students of class X Mathematics and Natural Sciences 1 and 34 students of class X Mathematics and Natural Sciences 2. Based on the results of the study, it was found that the results of the normality test were obtained for the control class posttest sig 0.11˃0.05 and the experimental class posttest obtained sig 1.22˃0.05 so that can be concluded to meet the normal assumptions. The results of the homogeneity test are sig 1.79˃0.005, which means the data is homogeneous. The results of the hypothesis test are obtained with a value of sig (2 tailed) = 0.000˂0.005, which means the research can be accepted or there is an influence. In other words, the implementation of Neighborhood Exploration (JAS) at the Tanjung Jabung Timur 9 State High School is very good and appropriate, greatly affecting learning outcomes, as evidenced by the implementation of the Surrounding Nature Exploration (JAS) learning which shows an average of 86.2 experimental posttest and 66.3 posttest control or good category. This shows that there is an influence between the Surrounding Nature Exploration (JAS) approach to student learning outcomes in the class X ecosystem material at SMP Negeri 9 Tanjung Jabung Timur.Keywords: Exploring the Surrounding Nature, student learning outcomes.